In Vitro Production of Smilax brasiliensis Seedlings, Callus Induction, Chemical Profile, and Assessment of Antioxidant Activity - Paula Avelar Amado; Ana Hortência Fonsêca Castro; Lucas Santos Azevedo; Mariana Guerra de Aguilar; Lúcia Pinheiro Santos Pimenta; Luciana Alves Rodrigues dos Santos Lima (Plants)
This study aimed to assess the production of Smilax brasiliensis seedlings in an in vitro environment and their adaptation to natural conditions, as well as the callus induction, the chemical profile of calli extracts, and their antioxidant potential. The seedlings were obtained from S. brasiliensis seeds germinated in Murashige and Skoog (MS) medium. The germination rate was 33%, and about 22% of the seeds produced whole seedlings. Three-month-old seedlings were acclimatized for two months, resulting in an 80% survival rate and improved physiological characteristics. Callus induction was initiated from leaf explants obtained from seedlings and plant growth regulators (PGRs), with and without light exposure. Calli extracts were obtained using methanol; phenolic compound and flavonoid quantification were performed, and the chemical profile was determined by nuclear magnetic resonance (1H NMR). For comparison, methanol extract from S. brasiliensis leaves collected in Brazilian Cerrado were also analyzed. Antioxidant activity was assessed using the 2,2-diphenyl-1-picryl-hydrazyl method and the ferric-reducing antioxidant power assay. All samples exhibited antioxidant activity according to the methods employed. Furthermore, 1H NMR revealed metabolic profile changes in the calli extracts compared to the leaf extract. This study yielded promising results, suggesting that in vitro culture could improve productivity and conserve the species, although changes were observed in the metabolic profile of S. brasiliensis.